Cancer immunotherapy by silencing transcription factor c-Rel using peptide-based nanoparticles - Lang, Shuyao; Zhu, Yuxuan; Tan, Zibin; Zhang, Yu; Liang, Ruijing; Ren, Jian; Li, Ping; Pan, Fan; Cai, Lintao; Chen, Youhai H. (Frontiers in Immunology, 2025)
BackgroundCancer immunotherapy has shown promising results in the clinic, but it faces great challenges such as low response rates and low efficacy in solid tumors. c-Rel, a member of the nuclear factor (NF)-κB family, is a newly described immune checkpoint for myeloid-derived suppressor cells (MDSCs), which contribute to the formation of immune-suppressive tumor microenvironment and resistance to cancer immunotherapy. How to selectively target myeloid c-Rel for the treatment of cancer is not well established. In this study, we investigated the feasibility and efficacy of knocking down myeloid c-Rel with siRNA-loaded peptide-based nanoparticles as a new cancer immunotherapy strategy.MethodsThe knockdown of c-Rel gene by the siRNA-loaded peptide nanoparticles was confirmed on MDSCs in vitro and in vivo. The effects of c-Rel silencing on cell number and immune suppressive function of the murine bone marrow-derived MDSCs were then investigated. To evaluate the anti-tumor efficacy of the c-Rel siRNA loaded nanoparticles, female C57BL/6 mice with subcutaneous B16 tumor were treated with PBS, c-Rel siRNA loaded nanoparticles, control siRNA loaded nanoparticles or empty nanoparticles. The tumor growth and body weight of mice were monitored, and the numbers and immune activities of tumor infiltrated immune cells in different groups were analyzed at the end of the experiment. The immune function of MDSCs isolated from tumor bearing mice received different treatments were further investigated ex vivo by T cell proliferation assays.ResultsThe c-Rel siRNA nanoparticles significantly reduced c-Rel expression in MDSCs, diminished both the number and immune suppressive function of MDSCs, and enhanced intratumor CD8+ T cell responses. Significantly reduced tumor growth was observed in mice treated with the c-Rel siRNA nanoparticles compared to control mice.ConclusionOur data indicates that peptide-based nanoparticles can be successfully utilized to target the myeloid immune checkpoint c-Rel for the treatment of cancer.